1969
DOI: 10.1172/jci106174
|View full text |Cite
|
Sign up to set email alerts
|

Very low density lipoproteins in intestinal lymph: origin, composition, and role in lipid transport in the fasting state

Abstract: A B S T R A C T The transport of endogenous lipids in the lipoproteins of mesenteric lymph was studied in fasting rats with mesenteric lymph fistulas. The lymph was found to contain, in addition to chylomicrons (Sf > 400), a significant amount of another, more dense, triglyceride-rich fraction, the very low density lipoproteins (VLDL), which showed a peak Sf of 102. The VLDL differed from chylomicrons not only in flotation, but also in per cent lipid composition and electrophoretic mobility in agarose gel. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

1972
1972
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(68 citation statements)
references
References 31 publications
2
65
0
1
Order By: Relevance
“…FFA released from CM-TG by LPL is converted efficiently to VLDL-TG in the liver (36)(37)(38). In rats, VLDL has been found in mesenteric lymph ( 39 ), and CM and VLDL are packed differently in the intestine ( 40 ), suggesting that increased VLDL production in the small intestine may occur in ddY mice.…”
Section: Discussionmentioning
confidence: 99%
“…FFA released from CM-TG by LPL is converted efficiently to VLDL-TG in the liver (36)(37)(38). In rats, VLDL has been found in mesenteric lymph ( 39 ), and CM and VLDL are packed differently in the intestine ( 40 ), suggesting that increased VLDL production in the small intestine may occur in ddY mice.…”
Section: Discussionmentioning
confidence: 99%
“…Even though this result was observed in an animal model of insulin resistance model, it was suggested that the endogenous production of fatty acids might influence the apoB-48-containing lipoprotein secretion in the small intestine. Endogenous lipids were secreted mainly in the fasting state in the size of VLDL (29), and almost half of total lymphatic TG was derived from endogenously synthesized sources in the postprandial state (30). It is known that PL in CM particles originates from the intestinal epithelium (31); therefore high PL contents of lipoproteins smaller than CM in size indicate that these lipoproteins might be derived from the endogenous source.…”
Section: Discussionmentioning
confidence: 99%
“…From the tubes that were supposed to contain CM remnants (tubes No. 11,14,17,20,23,26,29,32,35), 15 ml of flow-through (containing ?10 mg protein) was taken, subjected to 4-12% SDS-polyacrylamide gel electrophoresis (SDS-PAGE, TEFCO, Tokyo, Japan) and transferred onto the Immobilon-P Transfer membrane (Millipore Corp., Billerica, MA). This membrane was incubated with anti-human apoB-48 antibody and subsequently with anti-mouse IgG antibody (NA931V, GE Healthcare, Backinghamshire, UK).…”
Section: Lipoprotein Analysis By Hplcmentioning
confidence: 99%
“…The intestine as a source of plasma lipoReceived for publication 18 August 1975 and in revised form 13 November 1975. proteins was first suggested by biochemical studies which showed that the intestine could incorporate radioactive amino acids into lymph and plasma lipoproteins (1)(2). Studies of the composition of intestinal lymph indicated that the intestine can produce lipoproteins other than chylomicrons (3)(4)(5). Electron microscopic studies of rats have implicated the columnar absorptive cells as the particular site involved in intestinal very low density lipoprotein (VLDL) 1 production (6).…”
Section: Introductionmentioning
confidence: 99%